2016
DOI: 10.1016/j.intfin.2016.05.007
|View full text |Cite
|
Sign up to set email alerts
|

IPOs and SEOs, real investments, and market timing: Emerging market evidence

Abstract: This paper uses market-to-book ratio decomposition to examine whether firms that issue equity through initial public offerings or seasoned equity offerings exploit mispricing because of investor enthusiasm or to finance growth opportunities. We find strong evidence that, on average, firms do not issue mispriced stocks to exploit investors but, rather, to finance their investment opportunities in the form of real assets, inventory, and capital expenses. Firms that issue overvalued stocks with the view to increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…Menurut De Bondt dan Thaler (1987) yang meneliti mengenai market behavior dari investor, terjadi overreaction di capital market, terutama pada saat banyak terjadi peristiwa keuangan di suatu negara atau di dunia. Market overreaction tidak hanya terjadi pada peristiwa seperti IPO (Ritter, 1991), atau SEO (Wadhwa et al, 2016), namun juga ketika terdapat informasi baru yang beredar di publik mengenai suatu saham atau perusahaan. Market overreaction sendiri berarti fenomena saat investor cenderung memiliki reaksi berlebihan pada peristiwa atau informasi baru yang tidak terduga dan lebih memprioritaskan informasi tersebut dalam pengambilan keputusan daripada melihat data historis atau data yang selama ini telah ada.…”
Section: Faktor-faktor Yang Memengaruhi Initial Return Dan Performa Jangka Panjangunclassified
“…Menurut De Bondt dan Thaler (1987) yang meneliti mengenai market behavior dari investor, terjadi overreaction di capital market, terutama pada saat banyak terjadi peristiwa keuangan di suatu negara atau di dunia. Market overreaction tidak hanya terjadi pada peristiwa seperti IPO (Ritter, 1991), atau SEO (Wadhwa et al, 2016), namun juga ketika terdapat informasi baru yang beredar di publik mengenai suatu saham atau perusahaan. Market overreaction sendiri berarti fenomena saat investor cenderung memiliki reaksi berlebihan pada peristiwa atau informasi baru yang tidak terduga dan lebih memprioritaskan informasi tersebut dalam pengambilan keputusan daripada melihat data historis atau data yang selama ini telah ada.…”
Section: Faktor-faktor Yang Memengaruhi Initial Return Dan Performa Jangka Panjangunclassified
“…The second part of the review deals with the literature which investigated such issues, where most of the literature regarding such issues was related to the Chinese IPOs. From the literature (Moshirian et al, 2010;Liu et al, 2014;Espenlaub et al, 2016;Wadhwa et al, 2016;, we find that the level of under pricing is higher in countries with lenient regulatory environments and lower in countries with tighter regulations and higher transparency.…”
Section: Discussionmentioning
confidence: 89%
“…Finally, they reported that IPOs in countries with legal institutions originating in the UK common law system have nearly 40% longer survival times than those with civil law systems. Wadhwa et al (2016) included all IPOs and seasoned equity offerings (SEOs) listed on the Bombay Stock Exchange (BSE) and the National Stock Exchange from 1991 (the year of financial deregulation) to 2012. They examined whether equity issues through IPOs or SEOs were due to mispricing or growth opportunities.…”
Section: Regulatory Environment and Under Pricingmentioning
confidence: 99%
“…In addition, the value of Pdf_Folio:1282 a firm has been proven to be highly dependent on operating at optimal levels as well as equity market timing decisions by managers which impact decision-making [13]. However, the opposing situation is also evidenced in the literature where firms issuing during times of high equity valuations are driven by intentions to invest in real assets [14]. Thus, the findings from predictive model would also allow improved inferences to decision-making at investor and managerial levels.…”
Section: Introductionmentioning
confidence: 99%